Structural, spectroscopic, morphological and optical studies of new polymer composite based on polystyrene inserted with natural bitumen - Azhen S. Muhemmed; Shujahadeen B. Aziz (Scientific Reports)
Abstract In the current study, a breakthrough methodology has been utilized to deliver polymer composites based on polystyrene (PS) with enhanced optoelectronic properties. In this work, bitumen (BT), which is enriched with hydrocarbons and N/O elements extracted from natural rocks, has been employed to alter the optical band gap of the PS polymer. It was found that the optical parameters of PS improved significantly, which is crucial from the technological application viewpoint. The PS: BT films have been prepared utilizing a simple solution casting method. Fourier transforms infrared (FTIR), Raman spectroscopy, UV-absorption spectroscopy, and X-ray diffraction were used to investigate the effect of (BT) loading on the structural and optical properties of PS. The XRD analysis revealed that the addition of BT into PS improved the crystalline phase structure for the composite films. The D and G bands related to order and disorder structures were distinguished in the Raman spectra of the bitumen. The FTIR spectra demonstrated a shift and constriction of the PS-O-H stretching bands upon incorporating BT, indicating a robust interaction between BT and the polymer matrix. Furthermore, the FESEM images revealed rough surfaces in the composite films. Optical characterizations reveal that integrating BT into PS films enhanced their reflectance and diminished their transmittance of incident light at visible and ultraviolet wavelengths. The optical properties, including the absorption edge, refractive index, and dielectric constant, encompassing both the real and imaginary parts, were analyzed. The dielectric constant increased when comparing the composite samples to the pure polystyrene sample. The optical energy gap dropped from 4.34 to 1.14 as the BT doping concentration increased to 2 mL. The band edge width, which characterizes the tail-localized states, increases with higher BT concentration. The results of the present work will revolutionize the field of polymer composites for photonics and optoelectronics, especially non-linear optics and laser attenuation.